INTERNALIZING ISLAMIC VALUES IN PREVENTING BULLYING BEHAVIOR IN SCHOOLS - Dea Ayu Rozikin; Chusnul Muali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Bullying is a serious and frequent problem in schools, affecting the well-being of students and the environment, both physically, emotionally, and even socially. This incident must be addressed immediately to prevent school concerns during school activities. This study aims to prevent bullying cases in schools by internalizing Islamic religious values. By naming the feeling of loving each other and fostering noble character. This method uses a case study approach which is one of the research methodologies. In this case study, researchers must conduct a more thorough analysis of an event, in the form of individuals and groups. In addition to collecting data, researchers also observe and interview and understand the event holistically. The results of the study show that Islamic values provide a strong foundation for bullying cases, thus creating a safe, inclusive, and civilized learning environment. By consistently understanding and deepening Islamic values, students are also able to apply student character and tolerance attitudes so as to maintain relationships with each other, by providing examples of the attitudes of the prophets and Islamic figures. The application of Islamic religious values is also able to create a school environment that. Thus, concrete steps in internalizing religious values to prevent bullying cases involving all related parties, as well as evaluating the effectiveness of prevention strategies, can create a school environment based on the principles of justice, compassion and equality.